Provider verbal disrespect in the provision of family planning in public-sector facilities in Western Kenya - Katherine Tumlinson; Laura E. Britton; Caitlin R. Williams; Debborah Muthoki Wambua; Dickens Otieno Onyango; Leigh Senderowicz (Elsevier, 2022)
Public-sector healthcare providers in low- and middle-income countries are a primary source of family planning but their disrespectful (i.e., demeaning or insulting) treatment of family planning clients may impede free contraceptive choice. The construct of disrespect and abuse has been widely applied to similar phenomena in maternity care and could help to better understand provider mistreatment of family planning clients. With a focus on public-sector family planning provision in western Kenya, we aim to estimate the prevalence and impact of disrespect and abuse from a variety of perspectives and advance methodological approaches to measuring this construct in the context of family planning provision. We combine and triangulate data from a variety of sources across five counties in western Kenya, including 180 mystery clients, 253 third-party observations, eight focus group discussions, 19 key informant interviews, and two journey mapping workshops. Across both mystery client and third-party observations conducted in public-sector facilities in western Kenya, approximately one out of every ten family planning seekers was treated with disrespect by their provider. Family planning clients were frequently scolded for seeking family planning while unmarried or low parity, but mistreatment was not limited to women with these specific characteristics. Women were also insulted for such characteristics as body size or perceived sexual promiscuity. Qualitative data confirmed both that client disrespect is widespread and leads women to avoid family planning services even when they desire to use a contraceptive method, sometimes leading to unintended pregnancies. Key informants attribute disrespectful provider practices to both low technical skill as well as poor motivation stemming from both intrinsic values as well as extrinsic factors such as low wages and high caseloads. Possible solutions suggested by key informants included changes to recruitment and admission for Kenyan medical/nursing schools, as well as values clarification to shift provider motivations. Interventions to reduce mistreatment must be multi-layered and well-evidenced to ensure that family planning clients receive the person-centered care that enables them to achieve their contraceptive desires and reproductive freedom.